Photocatalyst- and additive-free decarboxylative alkylation of N-aryl tetrahydroisoquinolines induced by visible light. Issue 11 (24th March 2021) - Ma, Pengju; Liu, Yufei; Chen, Lingling; Zhao, Xu; Yang, Bo; Zhang, Junmin
Abstract : A photocatalyst- and additive-free visible light induced decarboxylative alkylation of N -aryl tetrahydroisoquinolines has been developed using tetrachloro- N -hydroxyphthalimide esters as alkylation agents. Abstract : A visible light induced decarboxylative alkylation of N -aryl tetrahydroisoquinolines has been developed using tetrachloro- N -hydroxyphthalimide esters as alkylation agents. This redox-neutral reaction can proceed without the assistance of photocatalysts, transition metals and external additives by irradiation with blue LEDs. Preliminary mechanistic studies indicated that this transformation probably proceeded through an electron donor–acceptor complex involved radical process.